PENGUKURAN BUDAYA ORGANISASI DAN PENGARUHNYA TERHADAP EFEKTIVITAS KEPEMIMPINAN DI SEKOLAH DASAR - Burhanuddin; Sunarni (Universitas Negeri Malang, 2017)
Abstract: This study aims at describing the tendency of the type of organizational culture and its impact on leadership effectiveness in elementary school. The design of research was using the research development involving 300 teachers as a sample and was selected purposively and proportional in five districts in Malang. The results showed that some types of organizational culture prevailed school organization including bureaucratic, supportive, innovative, market, adhocratic, and clan types. The entire types deem to be significant influence on the behavior and effectiveness of school leadership including the efforts of the principal in (1) the development of vision, mission, and organizational goals, (2) human resources management, (3) implementation of functions as manager, (4) role of leader, (5) the improvement of professional teacher, and (6) the development of school organizational climate. Abstrak: Penelitian ini bertujuan untuk mendiskripsikan kecenderungan tipe budaya organisasi dan pengaruhnya terhadap efektivitas kepemimpinan di sekolah dasar. Rancangan penelitiannya menggunakan penelitian pengembangan yang melibatkan 300 orang guru sebagai sampel yang dipilih secara purposive dan proportional dari lima kecamatan di Kota Malang. Hasil penelitian menujukkan sejumlah tipe budaya organisasi mewarnai organisasi sekolah meliputi tipe birokratis, supportif, inovatif, market, adhokrasi, dan klan. Kesemua tipe memiliki pengaruh signifikan terhadap perilaku dan efektivitas kepemimpinan sekolah meliputi usaha-usaha kepala sekolah dalam (1) pengembangan visi, misi, dan tujuan organisasi, (2) pengelolaan sumber daya manusia, (3) pelaksanaan fungsi sebagai manajer, (4) pelaksanaan peranan sebagai leader, (5) peningkatan professional guru, dan (6) pengembangan iklim organisasi sekolah.